Spatial and Temporal Variation in Fine Particulate Matter Mass and Chemical Composition: The Middle East Consortium for Aerosol Research Study. (18th June 2014) - Abdeen, Ziad; Qasrawi, Radwan; Heo, Jongbae; Wu, Bo; Shpund, Jacob; Vanger, Arye; Sharf, Geula; Moise, Tamar; Brenner, Shmuel; Nassar, Khaled; Saleh, Rami; Al-Mahasneh, Qusai M.; et al.
Abstract : Ambient fine particulate matter (PM2.5 ) samples were collected from January to December 2007 to investigate the sources and chemical speciation in Palestine, Jordan, and Israel. The 24-h PM2.5 samples were collected on 6-day intervals at eleven urban and rural sites simultaneously. Major chemical components including metals, ions, and organic and elemental carbon were analyzed. The mass concentrations of PM2.5 across the 11 sites varied from 20.6 to 40.3 μ g/m 3, with an average of 28.7 μ g/m 3 . Seasonal variation of PM2.5 concentrations was substantial, with higher average concentrations (37.3 μ g/m 3 ) in the summer (April–June) months compared to winter (October–December) months (26.0 μ g/m 3 ) due mainly to high contributions of sulfate and crustal components. PM2.5 concentrations in the spring were greatly impacted by regional dust storms. Carbonaceous mass was the most abundant component, contributing 40% to the total PM2.5 mass averaged across the eleven sites. Crustal components averaged 19.1% of the PM2.5 mass and sulfate, ammonium, and nitrate accounted for 16.2%, 6.4%, and 3.7%, respectively, of the total PM2.5 mass. The results of this study demonstrate the need to better protect the health and welfare of the residents on both sides of the Jordan River in the Middle East.